Hypervirulent Klebsiella pneumoniae clones causing bacteraemia in adults in a teaching hospital in Barcelona, Spain (2007–2013). (February 2016) - Cubero, M.; Grau, I.; Tubau, F.; Pallarés, R.; Dominguez, M.A.; Liñares, J.; Ardanuy, C.
Abstract: Virulent hypermucoviscous Klebsiella pneumoniae strains associated with the magA and rmpA genes have mainly emerged in Asia. We analysed the frequency and the clinical and molecular epidemiology of K. pneumoniae bacteraemia isolates obtained over a 7-year period (2007–2013). Fifty-three of 878 K. pneumoniae invasive isolates (5.4%) showed a hypermucoviscous phenotype (by the string test). Of these, 16 (30.2%) were magA + / rmpA +, 12 (22.6%) were magA − / rmpA +, and the remaining 25 (47.2%) were magA − / rmpA − . After multilocus sequence typing and wzi sequencing, all magA + / rmpA + isolates were serotype K1 and sequence type (ST)23. Of the 12 magA − / rmpA + isolates, nine were K2 (ST380, ST86, ST65, ST25 and ST493), and three magA − / rmpA + isolates had the new wzi allele 122, an unknown serotype, and the new ST1013. The remaining isolates, which were magA − / rmpA −, showed different serotypes and STs. Patients with magA + / rmpA + or magA − / rmpA + K. pneumoniae bacteraemia more frequently had pyogenic liver abscesses (PLAs) and pneumonia than patients with magA − / rmpA − K. pneumoniae bacteraemia (respectively: 21.4% vs. 8%, p 0.26; and 17.9% vs. 0%, p 0.05). In fact, magA − / rmpA − isolates were similar to the those termed 'classic' K. pneumoniae isolates causing bacteraemia, the urinary and biliary tracts being the main foci of infection. In conclusion, hypervirulent clones (CC23K1, CC86K2, CC65K2, and CC380K2) were infrequent among K. pneumoniae isolates causing bacteraemia in our geographical area. A hypermucoviscous phenotype as determined with the string test is not enough to recognize these clones; additional molecular studies are needed. Patients with magA + and/or rmpA + K. pneumoniae bacteraemia more frequently had PLAs and pneumonia than patients without hypermucoviscosity genes.